Meningkatkan Kemampuan Mahasiswa dalam Mengembangkan RPP Berdasarkan Kurikulum 2013 dengan Menggunakan â€œBloomâ€™s Taxonomy Cognitive Domain Learning Stagesâ€ pada Mahasiswa Semester VI FKIP Bahasa Inggris Universitas Kanjuruhan Malang - Fitri Anggraini Hariyanto (Jurnal Inspirasi Pendidikan, 2014)
The purpose of this study is to give detailed description about the model implementation of Bloom’s Taxonomy Cognitive Domain Learning Stages in the improvement of English students’ skill in creating the lesson plan based on the 2013 curriculum in Micro Teaching class. The implementation of Bloom’s Taxonomy Cognitive Domain Learning Stagesmodel is an effective and efficient strategy in training the students to develop the lesson plan. The strategy implementation also supports more cooperative learning situation since the students work together to analayze and evaluate the lesson plan and syllabus. This, it helps the students to understand the important steps in developing the lesson plan and opens the opportunity to discuss with others. This method combines the students’ individual skill improvement and cooperative skill in developing the lesson plan sistematically, well-coordinated and by clear steps. The result showed that the implementation of Bloom’s Taxonomy Cognitive Domain Learning Stages in improving the students’ skill in developing the lesson plan has achieved the criteria of success. It also contributes to the significant progress of the class average. Keywords: Bloom’s Taxonomy Cognitive Domain Learning Stages, CAR, Micro Teaching